الضغوط التي تواجه أستاذات التربية البدنية والرياضية في التعليم الابتدائي - رميشي حمزة, طوايبية ريم (My University, 2025)
ملخص الدراسة باللغة العربية ملخص البحث: العنوان: الضغوط التي تواجه أستاذات التربية البدنية والرياضية في التعليم الابتدائي . أهداف الدراسة : تهدف الدراسة الحالية الى: التعرف عن اهم مصادر و اعراض الضغوطات و انواعها التي تتعرض لها التربية البدنية و الرياضية في التعليم الابتدائي و العمل على ايجاد و اقتراح بعض الحلول للتقليل و التخلص من هذه الضغوطات إشكالية الدراسة والتي تنتهي بالتساؤل العام التالي: ماهي طبيعة الضغوط التي تواجهها استاذات التربية البدنية و الرياضية في التعليم الابتدائي و كيف تؤثر على أدائهن داخل المؤسسة ؟ فرضيات الدراسة : • تعاني الاستاذات من ضغوط نفسية نتيجة الشعور غياب الدعم النفسي داخل المؤسسة. • تواجه استاذات التربية البدنية والرياضية ناتجة عن ضعف الوسائل البيداغوجية و كثرة الاعباء الادارية و نقص التقدير المهني. • تؤدي طبيعة العمل في التربية البدنية و الرياضية الى ضغوط اجتماعية ناجمة عن النظرة النمطية تجاه الاستاذة و عدم التقبل المجتمعي الكافي لدورها. عينة الدراسة : أُجريت الدراسة الميدانية على 30 أستاذة للتربية البدنية و الرياضية للتعليم الابتدائي من المقاطعة الاولى و الثانية لولاية 2025 ، واختيرت العينة بطريقة عشوائية. - سوق أهراس، للعام الدراسي 2024 المنهج : استخدمت الدراسة المنهج الوصفي بأسلوبه التحليلي . أدوات الدراسة : - استمارة استبيان نتائج الدراسة :: أكدت النتائج أن استاذات التربية البدنية والرياضية في التعليم الابتدائي تواجه عدة ضغوطات نفسية ومهنية- واجتماعية abstract : ResearchSummary Title: The pressures faced by female physical education teachers in primary education. Objectives of the study: This study seeks to: Examine the key sources, manifestations, and types of stress experienced by physical education teachers at the primary school level, while proposing practical solutions to mitigate and overcome these stressors. The problem of the study: which ends with the following general question: "What types of pressures do female physical education teachers face at the primary school level?" Hypotheses of the study: • Female teachers suffer from psychological pressures due to a lack of emotional support within the institution. • Female physical education (PE) teachers face pressures stemming from inadequate teaching resources, excessive administrative burdens, and a lack of professional recognition. • The nature of work in physical education leads to social pressures caused by stereotypes toward female teachers and insufficient societal acceptance of their role. Study sample: This empirical study involved a randomly selected sample of 30 primary school physical education teachers (all female) from Districts 1 and 2 of Souk Ahras Province, with data collected during the 2024-2025 school year." Curriculum: The study used the descriptive approach with its analytical method Study Tools: Questionnaire form. The results of the study: Results indicated significant psychological, professional, and social pressures among female physical education teachers at the elementary level." Keywords: Stress.Physical and sportseducation. Femalephysicaleducationteachers. Primaryeducation résumé : Titre: Les pressions subies par les professeures d'éducation physique et sportive dans l'enseignement primaire." Objectifs de l’étude: "Cette étude vise à : Identifier les principales sources, manifestations et types de pressions subies par les enseignantes d'éducation physique et sportive (EPS) dans l'enseignement primaire, et à proposer des solutions pour les atténuer ou les éliminer. Le problème de l’étude: qui se termine par la question générale suivante: "Quelles sont les pressions subies par les enseignantes d'éducation physique et sportive (EPS) dans l'enseignement primaire ?" Hypothèses de l’étude: • Les enseignantes souffrent de pressions psychologiques dues au manque de soutien moral au sein de l’établissement. • Les professeures d’éducation physique et sportive (EPS) sont confrontées à des pressions liées au manque de moyens pédagogiques, à la lourdeur des tâches administratives et au manque de reconnaissance professionnelle. • La nature du travail en éducation physique et sportive engendre des pressions sociales résultant des stéréotypes à l’égard des enseignantes et d’un manque d’acceptation sociale de leur rôle. Échantillon de l’étude: "L'étude a été menée auprès de 30 enseignantes d'éducation physique et sportive (EPS) exerçant dans les écoles primaires des premier et deuxième districts de la wilaya de Souk Ahras, au cours de l'année scolaire 2024-2025. L'échantillon a été sélectionné de manière aléatoire." Programme d’études: L’étude a utilisé l’approche descriptive avec sa méthode analytique Outils d’étude:Formulaire de questionnaire Les résultats de l’étude: "Les résultats ont confirmé que les enseignantes d'éducation physique et sportive (EPS) dans le primaire sont confrontées à de multiples pressions d'ordre psychologique, professionnel et social."
دراسة ميدانية على بعض ابتدائيات ولاية سوق أهراس
Keywords: الضغوط; التربية البدنية والرياضية; استاذات التربية البدنية والرياضية; التعليم الابتدائي; Stress; Physical and sports education; Female physical education teachers